Chapter 9: Natural Toxins (Principles of Medical Toxicology, 2025)
SynopsisAuthorMrs. Sreedevi Kudaravalli, Associate Professor, Department of Pharmaceutical Biotechnology, Sultan-ul-Uloom College of Pharmacy, Banjara Hills, Hyderabad, Telangana, IndiaAbstractNatural toxins represent a diverse array of biologically active substances produced by plants, animals, fungi, and marine organisms that can cause significant morbidity and mortality. Plant toxins include cardiac glycosides found in oleander and foxglove that inhibit Na+/K+-ATPase, causing hyperkalemia and potentially lethal cardiac dysrhythmias. Anticholinergic plants like jimsonweed produce the classic toxidrome of hyperthermia, dry skin, urinary retention, and delirium. Ricinogenic plants contain potent cytotoxins causing severe gastrointestinal symptoms and potential organ failure. Animal venoms vary widely, with snake envenomations producing local tissue damage, coagulopathy, neurotoxicity, or cytotoxicity depending on species. Scorpion stings may cause intense pain or life-threatening cardiopulmonary effects, while spider bites range from local necrosis with recluse spiders to neurotoxicity with widow spiders. Mycotoxins demonstrate important timing distinctions, with early-onset mushroom poisonings typically causing gastrointestinal or neurological effects, while delayed-onset amatoxin poisoning leads to potentially fatal hepatorenal failure. Marine toxins include paralytic shellfish poisoning, ciguatera from reef fish, scombroid from improperly stored fish, and tetrodotoxin from pufferfish. Management emphasizes identification, symptom-specific supportive care, and administration of specific antidotes or antivenoms when available, with recognition that conventional toxicology screening rarely detects these diverse compounds.Keywords: Phytotoxins, Envenomation, Mushroom Poisoning, Antivenom, Cardiac Glycosides, Marine BiotoxinsVIEW PDF